PELAKSANAAN PENILAIAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 10 TUALANG DALAM BIDANG STUDI PENDIDIKAN JASMANI PADA MASA COVID 19 - Putri, Lila Septiana; Wijayanti, Ni Putu Nita; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is the use of assessment of learning outcomes during a pandemic through learning applications that are less relevant because not all information can be understood and executed by students, the main factor is hampered by an unstable internet network. The aim of this research was to determine the implementation of assessment of student learning outcomes in physical education during the covid-19 period. The population in this research was 57 students of class VIII. The sampling technique is total sampling. Based on the description of the results of the attitude competence assessment survey of 57 students, 37 students or 92.50% received the category very good. in the assessment of knowledge competence, no fewer than 36 students or 90% receive a good category. assessment of skills competences no less than 87.50% or 34 students get a very good category.Key Words: Student Outcome Assessment, Physical Education Learning During the Pandemic